Las mujeres y el poder en las organizaciones educativas. - Terrón Bañuelos, Aida; Valle Flórez, Rosa Eva; Díez Gutiérrez, Enrique Javier; Centeno Suárez, Begoña (Revista Complutense de Educación, 2002)
Sin resumen